Electric Mode Excitation in the Atmosphere by Magnetospheric Impulses and ULF Waves - Pilipenko, V. A.; Fedorov, E. N.; Martines-Bedenko, V. A.; Bering, E. A. (Frontiers in Earth Science, 2021)
Variations of vertical atmospheric electric field Ez have been attributed mainly to meteorological processes. On the other hand, the theory of electromagnetic waves in the atmosphere, between the bottom ionosphere and earth’s surface, predicts two modes, magnetic H (TE) and electric E (TH) modes, where the E-mode has a vertical electric field component, Ez. Past attempts to find signatures of ULF (periods from fractions to tens of minutes) disturbances in Ez gave contradictory results. Recently, study of ULF disturbances of atmospheric electric field became feasible thanks to project GLOCAEM, which united stations with 1 sec measurements of potential gradient. These data enable us to address the long-standing problem of the coupling between atmospheric electricity and space weather disturbances at ULF time scales. Also, we have reexamined results of earlier balloon-born electric field and ground magnetic field measurements in Antarctica. Transmission of storm sudden commencement (SSC) impulses to lower latitudes was often interpreted as excitation of the electric TH0 mode, instantly propagating along the ionosphere–ground waveguide. According to this theoretical estimate, even a weak magnetic signature of the E-mode ∼1 nT must be accompanied by a burst of Ez well exceeding the atmospheric potential gradient. We have examined simultaneous records of magnetometers and electric field-mills during >50 SSC events in 2007–2019 in search for signatures of E-mode. However, the observed Ez disturbance never exceeded background fluctuations ∼10 V/m, much less than expected for the TH0 mode. We constructed a model of the electromagnetic ULF response to an oscillating magnetospheric field-aligned current incident onto the realistic ionosphere and atmosphere. The model is based on numerical solution of the full-wave equations in the atmospheric-ionospheric collisional plasma, using parameters that were reconstructed using the IRI model. We have calculated the vertical and horizontal distributions of magnetic and electric fields of both H- and E-modes excited by magnetospheric field-aligned currents. The model predicts that the excitation rate of the E-mode by magnetospheric disturbances is low, so only a weak Ez response with a magnitude of ∼several V/m will be produced by ∼100 nT geomagnetic disturbance. However, at balloon heights (∼30 km), electric field of the E-mode becomes dominating. Predicted amplitudes of horizontal electric field in the atmosphere induced by Pc5 pulsations and travelling convection vortices, about tens of mV/m, are in good agreement with balloon electric field and ground magnetometer observations.